2022
DOI: 10.3389/fneur.2022.951850
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation in children with drug-resistant epilepsy of monogenic etiology

Abstract: Vagus nerve stimulation (VNS) is an effective treatment for drug-resistant epilepsy (DRE). The present study evaluated the efficacy of VNS in pediatric patients with DRE of monogenic etiology. A total of 20 patients who received VNS treatment at our center were followed up every 3 months through outpatient visits or a remote programming platform. The median follow-up time was 1.4 years (range: 1.0–2.9). The rate of response to VNS at 12 months of follow-up was 55.0% (11/20) and the seizure-free rate was 10.0% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…A total of 220 studies were identified through a comprehensive search of electronic databases and related bibliographies. The databases used for the search included Embase (150), Cochrane ( 7 ), PubMed ( 28 ) and CNKI ( 10 ). Based on the titles and abstracts, a total of 55 studies were deemed potentially eligible and selected for further evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 220 studies were identified through a comprehensive search of electronic databases and related bibliographies. The databases used for the search included Embase (150), Cochrane ( 7 ), PubMed ( 28 ) and CNKI ( 10 ). Based on the titles and abstracts, a total of 55 studies were deemed potentially eligible and selected for further evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been approved as a long-term treatment for DRE in children ( 8 ). VNS, a non-pharmacological intervention that enhances seizure control, has also been employed in the treatment of patients with DS ( 9 , 10 ). Studies have shown that VNS appears to be beneficial for children with SCN1A gene abnormalities associated with refractory epilepsy ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some knowledge is provided by the use of vagus nerve stimulation in the treatment of refractory epilepsy. Patients with RTT who underwent VNS displayed some side effects such as decreased appetite and coughing/choking on food, similar to patients with different diagnoses but not an exacerbation of their baseline breathing irregularities or cardiac complications (Wilfong and Schultz, 2006;Xie et al, 2022). In addition, the non-invasive tVNS, not employed in patients with this syndrome yet, could minimize typical side effects of invasive stimulation and increase tolerability.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 88%
“…A previous study demonstrated that VNS therapy improved cognitive disorder, autism and quality of life (QOL) in low-IQ patients (18). Furthermore, VNS was effective in pediatric patients with drug-resistant epilepsy (DRE) of monogenic etiology (19,20). In CDKL5-DEE, seizure improvement was reported in more than two-thirds of patients post-VNS therapy, and additional benefits such as cognitive and behavioral improvements justify further use in other gene-induced DEEs (21).…”
Section: Introductionmentioning
confidence: 99%